Trait-modified oils in foods - List, Gary R.; Orthoefer, Frank T., 1941- (Institute of Food Technologists series., 2015)
"In recent years, the food industry has made substantial advances in replacing partially hydrogenated oils, high in trans-fatty acids, in foods. Trait-modified oils were then developed to produce trans-fat free, low saturated functional oils. Trait-modified Oils in Foods offers top line information on the sources, composition, performance, health, taste, and availability of modified next generation oils. Coverage extends to public policy development, discussions of real world transition to healthy oils by food service and food processing industries and the future of trait-modified oils. The book provides solutions to food companies with the potential of improving the health benefits of foods through eliminating trans-fats and reducing saturated fats from formulations. A landmark resource on modified next-generation, trait-modified oils, this book is essential reading for oil processors, manufacturers and producers, as well as any professional involved in food quality assurance and public health"--